(3TQM QSGdI GHf CHj RjO GdbjQhGfis - (3YHO GdEdg Hf CMeO Hf GdMGL GdeUWai GdZdGhi GdTfbjWi GdMhVis; (3CHh eMeO YHO Gddg Hf CHj RjO GdeGdcj GdbjQhGfj,J (B389 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdHGbi HYO afGA Ndbg HSe Gddg GdQMef GdQMje aCJJM HgG EbJOGA HcJGH Gddg GdYRjR hgG CfG CTjQ ddaGcgGfi GdMeO Ci GdKfGA HGdhUa GdLejd KGHJ ddg s
(3BNQgG (B:s
(3bGd Udi Gddg Ydjg hSde (B( (3ef Sdc WQjbkG jdJeS ajg YdekG Sgd Gddg aVd GdYde Ydi GdYGHO caVd GdbeQ Ydi GdchGcH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3MhGa GdChQGb eJBcdI heJbUaIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs